MODEL EVALUASI PEMBELAJARAN BERBASIS KAIZEN DI SEKOLAH MENENGAH ATAS - Wijayati, Primardiana Hermilia; Suyata, Suyata; Sumarno, Sumarno (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2013)
Tujuan penelitian adalah mengembangkan model evaluasi pembelajaran yang hasilnya dapat digunakan untuk mendeteksi kekeliruan dan melakukan koreksi sendiri, serta sistem informasi-nya. Pengembangan dilakukan melalui pendekatan kuantitatif dan kualitatif dalam empat tahap, yaitu penelitian, penciptaan dan desain, rekayasa dan pengemasan, tahap pengujian dan evaluasi. Konstruk model evaluasi dimodifikasi dari model Marzano dan divalidasi melalui focus group discussion dan teknik Delphi. Subjek penelitian terdiri dari guru dan siswa di enam SMAN dan satu SMA swasta di Malang. Hasil penelitian: 1) model evaluasi didukung oleh instrumen evaluasi diri guru, evaluasi teman sejawat, dan evaluasi siswa; 2) karakteristik instrumen evaluasi mencakup validitas, reliabilitas, dan kepraktisan telah teruji; 3) sistem informasi hasil evaluasi disajikan dalam bentuk bar chart yang memuat informasi kelebihan dan kekurangan guru, rencana perbaikan guru, dan saran perbaikan untuk guru dan sekolah; 4) instrumen evaluasi berbentuk software disertai manualnya. Kata kunci: model evaluasi, kaizen, pembelajaran, sekolah menengah atas ______________________________________________________________A TEACHING EVALUATION MODEL BASED ON KAIZEN AT SENIOR HIGH SCHOOL Abstract This study aimed at developing an evaluation model to find out problems in the teaching process in order to prevent mistakes and to make a self-correction for assuring a continuous teaching improvement, and to deliver its information system. This was a development study which used quantitative and qualitative approaches carried out in four phases, namely initial research, invention and design, engineering and packaging, and test and evaluation. The construct of this evaluation model was adapted from Marzano's evaluation model and had been validated by a focus group discussion and Delphi technique. The subjects of this study were senior high school teachers and students from six public senior high schools (SMAN) and a private senior high school in Malang. This study shows the following conclusions: 1) The evaluation model based on kaizen has been equipped by self-evaluation instrument, evaluation instrument by colleagues and students; 2) The characteristics of the evaluation model based on kaizen for quality assurance of teaching at senior high school consisted of validity, reliability, and practicability which had been verified. The validity evidence had been obtained through focus group discussion and Delphi techniques, and had been analyzed using content validity ratio (CVR) and content validity index (CVI) proposed by Lawshe. The construct validity was elaborated through the structural equation modeling based on component; 3) The results of model fit test using GesCA-program developed by Heungsun Hwang indicate that the model is supported by the data shown by the value of GFI 0,997, and SRMR 0.076; 4) The information system of the evaluation results is presented in bar chart which accommodates teachers' strengths and weaknesses, teachers' planning of improvement, and suggestion of improvement for teachers and school.Keywords: development model, evaluation model, teaching process